Talent identification and development in judo: A perspective from Brazilian coaches - de Souza Ribeiro, A. A.; Werneck, F. Z.; Figueiredo, A. J. B.; Vianna, J. M. (International Journal of Sports Science and Coaching, 2023)
The knowledge of coaches is fundamental in the identification and development of sporting talents. The aim of the study was to investigate how Brazilian judo coaches identify talents and what is the importance of different factors for the development of young judokas. 56 coaches (87% male; 41.6 ± 12.5 years old; 64% Southeast region; 68% national/international competitive level) answered an online questionnaire about anthropometric, physical-motor, technical, tactical, psychological and environmental characteristics. On a scale of 1 (not very important) to 5 (extremely important), the coaches indicated to what extent a factor/indicator of sporting potential was important for talent development in judo. 58.9% of the coaches perform talent identification, mainly by training progression, competition performance and specific tests. The technical factor was the most important, followed by physical-motor, psychological and tactical, and finally environmental and anthropometric. Most of the coaches considered these indicators as extremely important: grip ability, projection, combination of attacks, transition from standing to ground fighting, reaction time, motor coordination, anaerobic endurance, lower limbs power, ability to withstand pressure, concentration and determination as well as practice quality and family support. It is concluded that Brazilian judo coaches identify talents mainly through training and competition and consider technique the most important factor for the development of talented young judokas.